OPTIMALISASI PERAN PERGURUAN TINGGI DALAM PEMBERDAYAAN MASYARAKAT - MUHAMAD RUDI WIJAYA (Najah Bestari, 2022)
Higher education is an educational institution that prepares students to become members of the community who have both academic and skill abilities. As a place of education for the nation's generation. Universities have a very important role in character building and are expected to be able to produce quality graduates so that they are able to bring the Indonesian nation towards a more advanced direction. In implementing higher education, it refers to the Tri Dharma of Higher Education, including education, research, and community service. With regard to community empowerment, this is related to the third Tri Dharma Perti point, namely community service. all knowledge that has been obtained in academic activities during lectures where the knowledge gained can be used for community empowerment. Higher Education is the pioneer in fostering and developing integrated human resources in order to meet (1) the needs of citizens who are ideally oriented towards education, through the creation of a conducive environment for the growth of a dynamic academic spirit, and can become a vehicle for socializing values, norms, and values. and independent attitude, and (2) pragmatic-oriented community needs through the readiness to educate people who can be absorbed by the business world according to their respective specifications.